Practice and Prospects of Medium-term Economic Forecasting - Helmut Hofer; Torsten Schmidt; Klaus Weyerstrass (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
Government agencies and other national and international institutions are asked to perform forecasts over the medium term. In particular, the EU Stability and Growth Pact contains the obligation to formulate stability programmes over four years, covering a general economic outlook as well as the projected development of public finances. However, the current practice of performing medium-term economic projections is unsatisfactory from a methodological point of view as the applied methodology has been developed for short-run forecasting and it is questionable whether these methods are useful for the medium term. In particular, currently medium-term projections are mostly based on the neoclassical Solow growth model with an aggregate production function with labour, capital, and exogenous technological progress. It might be argued, however, that for medium-run projections endogenous growth models might be better suited. In this paper we give an overview of currently used methods for medium-term macroeconomic projections. Then we analyse the performance of medium-term forecasts for Austria to illustrate the strengths and weaknesses of the typical approach. In particular, the five-year projections of real GDP growth, inflation and the unemployment rate are investigated. Finally, we describe some approaches to improve medium-run projections. – – Regierungen sowie nationale und internationale Organisationen haben ein Interesse daran, Wirtschaftsprognosen über die mittlere Frist zu erstellen. So verpflichtet der europäische Stabilitäts- und Wachstumspakt die Mitgliedstaaten des Euroraums dazu, jährliche Stabilitätsprogramme mit Vier-Jahres-Projektionen der wirtschaftlichen Rahmenbedingungen und der Entwicklung des Staatshaushalts zu liefern. Die gegenwärtige Praxis der Erstellung mittelfristiger Wirtschaftsprojektionen kann dahingehend kritisiert werden, dass die verwendeten Methoden primär für kurzfristige Prognosen entwickelt wurden, während in der mittleren Frist andere Faktoren als für die kurzfristige Wirtschaftsentwicklung relevant sein könnten. In der Regel basieren die Mittelfristprojektionen auf dem Solow-Modell mit einer gesamtwirtschaftlichen Produktionsfunktion mit den Einsatzfaktoren Arbeit, Kapital und exogener technischer Fortschritt. Es könnte jedoch argumentiert werden, dass für die mittlere Frist das endogene Wachstumsmodell besser geeignet sein könnte. In diesem Beitrag geben wir zunächst einen Überblick über den aktuellen Stand der Methoden mittelfristiger Wirtschaftsprojektionen. Anschließend analysieren wir die mittelfristigen Projektionen für Österreich, um die Stärken und Schwächen des üblicherweise verwendeten Ansatzes zu illustrieren. Im Speziellen untersuchen wir die Fünf-Jahres-Prognosen des realen BIP-Wachstums, der Inflationsrate und der Arbeitslosenquote. Schließlich beschreiben wir einige Ansätze, mit deren Hilfe Mittelfristprojektionen verbessert werden könnten.
Keywords: C53; E32; E37; E66; 330; Econometric models; macroeconomic forecasts; aggregate production function; Austria; Wirtschaftsprognose; Prognoseverfahren; Theorie; Österreich